A MODIFICATION OF ARTIFICIAL BEE COLONY ALGORITHM FOR SOLVING INITIAL VALUE PROBLEMS - Gunel, K; Gor, I (TWMS journal of applied and engineering mathematics, 2019)
In this paper, some improvements have been made on Artificial Bee Colony (ABC) algorithm to get numerical solutions of both linear and nonlinear differential equations as initial value problems. The solutions are obtained by a feed-forward neural network trained by the modified ABC. Keywords: Initial Value Problems, Ordinary Differential Equations, Global Optimization, Artificial Bee Colony. AMS Subject Classification: 68T20, 68T05, 65L05